Money, football and politics: Asiagate and the scourge of match-fixing in Zimbabwe - Chiweshe, Manase Kudzai (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Football is the most popular game in Zimbabwe. Events and activities in this sport in many ways mirror the state of wider society in the country. This paper provides a grounded critique of how money, football and politics intersect through the lens of the Asiagate match-fixing scandal which engulfed post-2000 Zimbabwe. It utilizes reports and transcripts from the investigation to highlight the role of various actors in the match-fixing scandal including administrators, politicians, coaches, players, referees, and journalists.
Keywords: match-fixing; Asiagate; football; Zimbabwe